The Adjective in Sacred Hadiths (A Grammatical Study) - kaddum, mohamed; Mega Mohamed, Abu Bakr; Mahra, Bassam (El Omda in Linguistics and Discourse Analysis, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-(–header-height)" dir="auto" data-turn-id="9f178e0c-824a-4d56-a7b8-2033d393ced4" data-testid="conversation-turn-159" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:d5b1c4d3-357e-4700-8347-cbb529b42195-79" data-testid="conversation-turn-160" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="21781372-0fb4-46e3-b94a-4941ffe228bf" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> This study examines “the adjective (na‘t) in Sacred Hadiths” as a grammatical investigation, drawing on the book Jami‘ al-Ahadith al-Qudsiyyah in order to identify the various adjectival structures found in sacred prophetic traditions, as explained by grammarians. It also aims to clarify the different forms in which these structures appear in the hadiths and the extent of their relationship with linguistic contexts. This research is of particular importance because it addresses Sacred Hadiths within a single independent study through the book Jami‘ al-Ahadith al-Qudsiyyah, focusing specifically on the adjective as a grammatical phenomenon. To date, it has not been treated as an independent study by grammarians or researchers. An inductive analytical method was adopted due to its suitability for the subject of the research. In the conclusion, the most important findings and recommendations are presented.